Registry for Evaluating Healthy Life Expectancy and Long-Term Outcomes after Catheter Ablation of Atrial Fibrillation in the Very Elderly (REHEALTH AF) study: rationale and design of a prospective, multicentre, observational, comparative study. Issue 2 (15th February 2023) - Okumura, Yasuo; Nagashima, Koichi; Watanabe, Ryuta; Yokoyama, Katsuaki; Kato, Takeshi; Fukaya, Hidehira; Hayashi, Hidemori; Nakahara, Shiro; Shimizu, Wataru; Iwasaki, Yu-ki; Fujimoto, Yuhi; Mukai, Yasushi; et al.
Abstract : Introduction: Data are lacking on the extent to which patients with non-valvular atrial fibrillation (AF) who are aged ≥80 years benefit from ablation treatment. The question pertains especially to patients' postablation quality of life (QoL) and long-term clinical outcomes. Methods and analysis: We are initiating a prospective, registry-based, multicentre observational study that will include patients aged ≥80 years with non-valvular AF who choose to undergo treatment by catheter ablation and, for comparison, such patients who do not choose to undergo ablation (either according to their physician's advice or their own preference). Study subjects are to be enrolled from 52 participant hospitals and three clinics located throughout Japan from 1 June 2022 to 31 December 2023, and each will be followed up for 1 year. The planned sample size is 660, comprising 220 ablation group patients and 440 non-ablation group patients. The primary endpoint will be the composite incidence of stroke/transient ischaemic attack (TIA) or systemic embolism (SE), another cardiovascular event, major bleeding and/or death from any cause. Other clinical events such as postablation AF recurrence, a fall or bone fracture will be recorded. We will collect standard clinical background information plus each patient's Clinical Frailty Scale score, AF-related symptoms, QoL (Five-Level Version of EQ-5D) scores, Mini-Mental State Examination (optional) score and laboratory test results, including measures of nutritional status, on entry into the study and 1 year later, and serial changes in symptoms and QoL will also be secondary endpoints. Propensity score matching will be performed to account for covariates that could affect study results. Ethics and dissemination: The study conforms to the Declaration of Helsinki and the Ethical Guidelines for Clinical Studies issued by the Ministry of Health, Labour and Welfare, Japan. Results of the study will be published in one or more peer-reviewed journals. Trial registration number: UMIN000047023.